Identifying factors for the poor public institutions performance in portuguese construction industry - Couto, J. Pedro (2011)
The lack of competitiveness of the Portuguese construction industry has been recurrently mentioned in the press and in technical literature. The duration of construction projects right from inception to completion is assuming great importance in the construction industry. A national survey on construction delays concluded that one of the main causes for construction delays is the recurrent lack of coordination and delays from the promoting institutions. From 118 causes for delays, 3 connected with public institutions performance and relationships are within the 15 most relevant. This paper critically discusses the problem of poor institutional performance in Portugal using literature and data from a set of interviews inserted in a national survey with expert construction managers. The main factors for the poor performance of those institutions will be established. A number of measures will be then identified in order to lessen the problem.